2017
DOI: 10.1136/bcr-2017-220416
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related hypogonadism: a reversible condition

Abstract: Obesity is associated with hypogonadism. While this association is widely accepted, the underlying mechanisms remain unclear. Furthermore, obesity is a risk factor for hypogonadism and conversely hypogonadism may be a risk factor for obesity. We present the case of a morbidly obese man aged 30 years with hypogonadotrophic hypogonadism that underwent a Roux-en-Y gastric bypass operation. Following the surgical treatment of his obesity, the testosterone level returned to normal with improvements in hypogonadal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Morbidly obese men that underwent a Rouxen-Y gastric bypass operation noticed an improvement in their testosterone level with improvements in hypogonadal symptoms, which allowed discontinuation of exogenous testosterone therapy. This demonstrates reversal of hypogonadism following weight loss with restoration of gonadal function [5].…”
Section: Introductionmentioning
confidence: 73%
“…Morbidly obese men that underwent a Rouxen-Y gastric bypass operation noticed an improvement in their testosterone level with improvements in hypogonadal symptoms, which allowed discontinuation of exogenous testosterone therapy. This demonstrates reversal of hypogonadism following weight loss with restoration of gonadal function [5].…”
Section: Introductionmentioning
confidence: 73%
“…It is also associated with increased SHGB and decreased estrogen levels [106,107,108]. These benefits occur regardless of the method of weight loss, whether through lifestyle/dieting or bariatric surgery, but they are more pronounced following the latter, since more weight loss is often achieved through bariatric surgery than lifestyle changes [107,109,110]. Multiple studies show that the increase in, F.T.…”
Section: Treatment Of Hypogonadismmentioning
confidence: 99%
“…A recent meta-analysis found that in individuals with obesity who subsequently lost weight, TT rose more significantly in younger males than in older males, further emphasizing the importance of weight loss interventions to treat hypogonadism in adolescent males with obesity [106]. Weight loss in men with hypogonadism has also been shown to improve erectile function [109,110]. Weight loss medications also contribute to the reversal of hypogonadism, and their effects are most pronounced when used as adjunctive therapy to bariatric surgery [110,111,112].…”
Section: Treatment Of Hypogonadismmentioning
confidence: 99%
See 1 more Smart Citation